Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
What is log675 with base 5 × log 3 with base 3?
We have to calculate (log 675 to the base 5) × (log 3 to the base 3)
Note the following important points :
(1.) log 675 to the base 5
=> log 675 to the base ‘e’ / log 5 to the base ‘e’
=> ln 675 / ln 5
Since 675 = 5^2 × 3^3
=> ln 675 = ln [5^2 × 3^3]
=> ln (5^2) + ln (3^3)
=> 2 ln 5 + 3 ln 3
Hence, log 675 to the base 5
= ln 675 / ln 5
= [2ln 5 + 3ln 3] / ln 5
(2.) Similarly, log 3 to the base 3
=> Since the logarithm of any natural number 'x' to the base of same number 'x' is always 1 (since any natural number raised to the power '1′ is equal to the same number) ,
Thus, (log 3 to the base 3) = 1
Hence, our problem reduces to:
(log 675 to the base 5) × (log 3 to the base 3)
=> [(2ln 5 + 3ln 3) / ln 5] × (1)
=> (2ln 5 + 3ln 3) / ln 5
=> So we only require the values of natural logarithm of 3 and 5 :)
We should remember these values, or we can always use log table.
Since ln 3 = 1.098
and ln 5 = 1.609
=> 2ln 5 = 2(1.609) = 3.218
=> 3ln 3 = 3(1.098) = 3.294
Hence,
solution : (3.218 + 3.294) / 1.609
=> 6.512 / 1.609
=> 4.047
GLAD TO HELP YOU ;))
We have to calculate (log 675 to the base 5) × (log 3 to the base 3)
Note the following important points :
(1.) log 675 to the base 5
=> log 675 to the base ‘e’ / log 5 to the base ‘e’
=> ln 675 / ln 5
Since 675 = 5^2 × 3^3
=> ln 675 = ln [5^2 × 3^3]
=> ln (5^2) + ln (3^3)
=> 2 ln 5 + 3 ln 3
Hence, log 675 to the base 5
= ln 675 / ln 5
= [2ln 5 + 3ln 3] / ln 5
(2.) Similarly, log 3 to the base 3
=> Since the logarithm of any natural number 'x' to the base of same number 'x' is always 1 (since any natural number raised to the power '1′ is equal to the same number) ,
Thus, (log 3 to the base 3) = 1
Hence, our problem reduces to:
(log 675 to the base 5) × (log 3 to the base 3)
=> [(2ln 5 + 3ln 3) / ln 5] × (1)
=> (2ln 5 + 3ln 3) / ln 5
=> So we only require the values of natural logarithm of 3 and 5 :)
We should remember these values, or we can always use log table.
Since ln 3 = 1.098
and ln 5 = 1.609
=> 2ln 5 = 2(1.609) = 3.218
=> 3ln 3 = 3(1.098) = 3.294
Hence,
solution : (3.218 + 3.294) / 1.609
=> 6.512 / 1.609
=> 4.047
GLAD TO HELP YOU ;))
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.